Characterization of breast imaging education and insights from students, radiographers and teaching staff about its strengths, difficulties and needs. Issue 1 (February 2019) - Sá dos Reis, C.; Strøm, B.; Richli-Meystre, N.; Pires Jorge, J.A.; Henner, A.; Kukkes, T.; Metsälä, E.
Abstract: Introduction: The study aimed to characterize breast imaging education and identify its strengths, difficulties and needs across five European countries according to student, radiographer and teaching staff perspectives. Methods: An observation grid was used to collect data regarding breast imaging education and three questionnaires targeted to key-participants were developed/applied to collect data on strengths, difficulties and needs. Descriptive statistics and thematic analysis were performed according to the nature of the questions. Results: Breast imaging curricula varied within and between countries. Response rate for questionnaires also varied (13–100%). More than one-third of the teaching staff (37.5%) was involved in breast research projects. This was identified as the main strength in breast imaging education followed by collaborations between hospitals and academia. Difficulties with their education program identified by the 97 students surveyed included teaching issues (45), breast positioning (18), variety of image evaluation strategies (10) and human interaction (6). The need to provide an explanation to the patient about the role of the student in the mammography setting, and performing exams and teaching at the same time (22.6%) was identified as difficult by radiographers. The need for education and training in communication, practice and technological developments was identified. Conclusions: A bridge between academia and clinical practice is extremely important in order to overcome recognized gaps between theory and practice. The development of a European education program covering the needs identified by the participants could be a possible solution to improve knowledge and access, and also to harmonize education and training across Europe. Highlights: Breast imaging curricula varies within and between countries. Mammography research was considered a strength in education and training. Main difficulties in education: breast positioning, human interaction. Limited time period allocated to mammography education was highlighted. Need of education and training in communication and new technologies.